2012
DOI: 10.1128/jb.06804-11
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Dairy Isolate Streptococcus macedonicus ACA-DC 198

Abstract: The species Streptococcus macedonicus is associated with the food environment, especially with fermented dairy products. Here we present the complete 2.1-Mb genome sequence of strain ACA-DC 198, which was isolated from naturally fermented Greek kasseri cheese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…This would allow for determining particular species which contain a desirable gene cluster, such as biogenic amine gene clusters. Examples of cheese associated microbes sequenced include, Lactobacillus cypricasei KCTC 13900 (Kim et al, 2011), Corynebacterium casei UCMA 3821 (Monnet et al, 2012), Streptococcus macedonicus ACA-DC 198 (Papadimitriou et al, 2012), and Corynebacterium variabile DSM 44702 (Schroder et al, 2011) among many others.…”
Section: New Detection Methods: Next Generation Sequencing (Ngs)mentioning
confidence: 99%
“…This would allow for determining particular species which contain a desirable gene cluster, such as biogenic amine gene clusters. Examples of cheese associated microbes sequenced include, Lactobacillus cypricasei KCTC 13900 (Kim et al, 2011), Corynebacterium casei UCMA 3821 (Monnet et al, 2012), Streptococcus macedonicus ACA-DC 198 (Papadimitriou et al, 2012), and Corynebacterium variabile DSM 44702 (Schroder et al, 2011) among many others.…”
Section: New Detection Methods: Next Generation Sequencing (Ngs)mentioning
confidence: 99%
“…Genome sequencing of a dairy isolate of S. macedonicus revealed that the bacterium is undergoing regular genome decay as indicated by the presence of a large number of pseudogenes. The genus also appears to lack the pil1 locus that is involved in instances of infectious endocarditis caused by pathogenic relatives (Papadimitriou et al, 2012). Nonetheless, further investigations are required to definitively establish the safety status of the species with respect to its use in dairy products.…”
Section: Streptococcusmentioning
confidence: 99%
“…Interestingly, Streptococcus macedonicus ACA-DC 198 (designated S. gallolyticus subsp. macedonicus in this study according to [3]), a Greek cheese isolate, displayed comparable genome decay to S. thermophilus and could indicate parallel evolutionary adaptation to the dairy environment in other members of the SBSEC and important contributions of certain members of the SBSEC to dairy fermentations in Europe [30]. …”
Section: Introductionmentioning
confidence: 97%